Effect of surface modification of pure Ti on tribological and biological properties of bone tissue. (1st May 2013) - Qi, H; Wu, H Y
<x xml:space="preserve">Abstract</x> Surfaces are the primary place of contact between bone and implant without an intervening soft tissue layer. Titanium based alloys are widely used for orthopaedic implants due to their high biocompatibility and high corrosion resistance. However, pure Ti is a soft material with a low shear resistance, and its poor wear resistance limits its application. TiO2 biological coating has not yet been produced by double glow plasma surface alloying, which is a technique based on both ion nitriding and sputtering. Wear resistance and blood compatibility of materials were studied in this paper. The results showed that friction coefficient and wear rate of oxygenised layer were lower than that of the matrix. In the dynamic clotting time, uniform rutile TiO2 (1 0 1) film after plasma oxygenising due to high electron density, low cavity density and electrostatic attraction of Ca2+ ions on the TiO2 surface exhibited the best biocompatibility.